Resolution 2024-05 : Cellphone Ban - Quebec Federation of Home and School Associations (QFHSA) (2024)

Résolution 2024-05 : Interdiction d’utiliser un téléphone cellulaire - Quebec Federation of Home and School Associations (QFHSA) (2024)

Access to Justice in English Project : Access to Quebec government websites in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

Projet Accès à la justice en anglais : Accès aux sites Web du gouvernement du Québec en anglais : Rapport exécutif et recommandations - Quebec Community Groups Network (QCGN) (2023)
Le projet Accès à la justice en anglais du QCGN (« le Projet ») repère et recherche les domaines où la communauté d’expression anglaise éprouve des difficultés à accéder à ses droits en mettant l'accent sur l'accès des communautés aux services publics. Il utilise l'information comme une ressource stratégique pour comprendre et améliorer l'accès à la justice en anglais au Québec.

Fraud : What you should know - Assistance and Referral Centre (ARC) (2022)

Press Release : Making Homemade Tomato Sauce with Greg on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Author Conversations with Richard King on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Organic Gardening with Hannah on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Tango Dancing with Mireille & Friends on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Making Jam with Susan on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : The Flamboyant World of Drag with Barbada on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Community Organization of Lanaudière (ECOL) (2021)

Press Release : Wine Pairing with Ana on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Horse Therapy with Karine on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Indigenous Hoop Dancing with Makhena on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2021)
Number of pages: 4

Press Release : Animal Fostering with Cindy on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Spring Special! Gardening in Small Spaces on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Flower Arranging on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Laughter Yoga on We’re All In This Together, the Web Series for Seniors - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New Episode of Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : New York Times Bestselling Author Louise Penny Is The Guest of the Web Series for Seniors We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : Celebrated New York Times Bestselling Author Louise Penny, on Senior’s Web Series We’re All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2021)

Press Release : A Holiday Concert of Quebec Performers at Martha Wainwright's URSA Follows Incredibly Popular First Episode of "We're All In This Together" - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Press Release : Launch of Project We Are All In This Together - Seniors Action Quebec (SAQ); English Language Arts Network (ELAN) (2020)

Validate ARTS2U Business Model - VABM Research Report - English Language Arts Network (ELAN) (2020)
With this research, the ELAN ARTS2U project has described comprehensive business and revenue modelling for the digital events listings service in the arts sector. This project supports science research of new technology models for the arts sector with potential to enhance and promote increased tourism in Canada. It is building on the scientific premises of metadata, natural language processing, machine learning and AI to the benefit of Canadian creative productions. It improves the potential for investment in Canadian locations and has the potential to develop employment positions in the high skilled technology job market. ARTS2U and its national collaborators are building an efficient and competitive Arts sector marketplace. By driving innovation in the arts and creative sectors, the ARTS2U initiative demonstrates that Canada is a leader in the international creative economy.

Research Project : Prototype Digital Solutions (ARTS2U) Final Report - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2019)
Between August 2018 and March 2019, ELAN's Prototype Digital Solutions research project conducted prototype development toward a more effective digital marketing system for Quebec-based English-language arts producers. For the purpose of communications and marketing, and as a unifying title for the prototype and the research components, the project uses the working title of ARTS2U .
Keywords: Official Language Minority Community (OLMC)

Digital Solutions to Connect Artistic Producers with Cultural Consumers - English Language Arts Network (ELAN) (English-Language Arts Network (ELAN), 2018)
Between January and March 2018, ELAN's Digital Solutions research project surveyed artists, arts organizations, publicists, journalists, media specialists and technical specialists, and hosted two focus group sessions.

Écoles québécoises en ligne : Un monde de possibilités pour l'éducation en langue anglaise - Advisory Board on English Education (2014)
En 1996, la Commission de l’éducation en langue anglaise (CELA) a déposé un mémoire sur l’intégration des technologies de l’information et de la communication (TIC) dans les écoles anglophones dans lequel elle souligne les besoins particuliers de ces établissements, notamment en milieu rural, et formule des recommandations sur des sujets comme l’accessibilité de ces nouveaux outils, le soutien aux enseignants et l’organisation scolaire. Les membres actuels de la CELA constatent l’ampleur et le rythme des progrès technologiques depuis 1996, mais continuent d’avaliser en principe le contenu du document antérieur, forts d’une conviction profonde que la technologie reste subordonnée à la pédagogie. Il n’en reste pas moins que la technologie présente dans la classe a changé à un rythme qui était inimaginable à cette époque. Les changements sont qualitatifs autant que quantitatifs et appellent donc une discussion entre toutes les parties prenantes sur son interaction avec la pédagogie, au vu de l’évolution de notre compréhension de l’enseignement et de l’apprentissage. Par ailleurs, les problèmes que posent aux écoles et aux centres de formation anglophones la composition et la dispersion de la population ainsi que la distance se font plus aigus et nécessitent des solutions ingénieuses si l’on veut que les diplômés soient prêts pour le XXIe siècle, et les solutions que peuvent fournir les TIC méritent discussion. Le présent mémoire porte sur la situation générale, mais aussi sur les questions qui touchent particulièrement le système d’éducation en langue anglaise du Québec. Il contient un ensemble de recommandations destinées à guider le Ministère dans la formulation de ses orientations.

Québec Schools On Line : Opportunities for English-Language Education - Advisory Commitee for English-Speaking Quebecers (2014)
In 1996, The Advisory Board on English Education (ABEE) prepared a brief on the integration of technology into English language schools, noting the particular needs of these schools, especially in rural areas, and making recommendations on accessibility, teacher support, and school organization, among other issues. The current Board notes how much—and how quickly— the technology has changed since 1996 but, based on its strongly held belief that technology is subordinate to pedagogy, it endorses in principle the content of this earlier document. Yet the technology available for classroom use has changed, it has done so at a speed unimaginable in 1996, and done so qualitatively as well as quantitatively, making it imperative that a broad-based discussion of technology in teaching take place as part of our changing understanding of teaching and learning. In addition, the problems in English language schools and centres caused by demographics, distance and dispersion have become more acute and more in need of ingenious solutions so that their graduates are prepared for the 21st century, and potential solutions to these problems through Information and Communications Technologies (ICT) merit discussion. This brief addresses both the general issues and those pertinent to the English education system in Québec, and includes a set of recommendations to help in the formulation of MELS orientations.

Gender-based Approach to Women in Technology Project: Women in Technology : Final Report - Wood, Andrea (2013)
This paper represents the research component of a larger project focusing on “women in technology”, an initiative launched by YES Montreal in autumn 2012. The project strives to build capacity in Montreal’s technology sector by applying a gender-based analysis in the advocacy of women’s career development in the technology sector. The research will support the delivery of programs focusing on the development, implementation and evaluation of women’s careers in technology over a 3-year period, between 2013 and 2015.

Women in Technology - Wood, Andrea (Youth Employment Services (YES), 2013)
This paper represents the research component of a larger project focusing on “women in technology”, an initiative launched by YES Montreal in autumn 2012. The project strives to build capacity in Montreal’s technology sector by applying a gender-based analysis in the advocacy of women’s career development in the technology sector. The research will support the delivery of programs focusing on the development, implementation and evaluation of women’s careers in technology over a 3-year period, between 2013 and 2015. The Montreal technology sector faces a pipeline issue. This report aims to improve the understanding of the factors influencing the technology sector’s lifecycle, from elements impacting early technology education through career development. Predominantly, the research addresses the issues that prevent women in Quebec’s technology sector from achieving their goals. In order to elaborate upon the issues and opportunities, the study relies on two forms of research: secondary research conducted by experts in the field, and primary data collected through surveys, focus groups and interviews.
Parallel title: Gender Based Analysis : Technology Sector in Quebec

Study on the Use of the Internet, New Media and Social Media and Respect for Canadians' Language Rights : A Study on Air Canada's Obligations Under the Offiicial Languages Act - Quebec Community Groups Network (QCGN) (2011)
Parallel title: Remarks to the Standing Committee on Offical Languages

Remote Site Information Technology Assessment for the Municipality of Bonne-Esperance Lower North Shore, Quebec - Coasters Association (2004)
Information technologies (computers, Internet, etc.) are an essential component of modern economic development strategies. The Lower North Shore has lagged behind other areas in terms of equipment, infrastructure and human resource capacity for using information technologies as an integral part of their community development efforts (i.e. no hi-speed access.) Recent innovations in this area allow for the reception of hi-speed (broadband) Internet reception via satellite; with establishment of local area networks (LANs) connected to each satellite point-of-delivery, the prospect exists for significant improvements to the information technology capacity of remote locations such as MBE, as well as local revenue generation from service provision once the LAN is established.

Alliance Quebec Condemns the Office de la langue française's Attempt to Impose Francization Requirements on Commercial Websites Produced in Quebec - Alliance Quebec (AQ) (1999)

L'intégration des nouvelles technologies de l'information et de la communication dans les écoles anglaises du Québec - Advisory Board on English Education (1997)
Étant donné la réforme de l'éducation et la pression croissante qui pousse à intégrer les nouvelles technologies de l'information et de la communication (NTIC) à l'enseignement et à l'apprentissage, la Commission de l'éducation en langue anglaise a voulu identifier les facteurs propices et les obstacles à une mise en oeuvre efficace des progrès technologiques. Son but est de permettre aux écoles anglaises de tirer pleinement parti de ces nouveaux outils et d'améliorer réellement l'apprentissage. À cette fin, elle s'est concentrée sur les quatre éléments du processus éducatif qui paraissent les plus susceptibles de changement, soit le rôle du personnel enseignant, l'apprentissage, l'organisation de l'école et la nécessité d'étendre l'actuel réseau informatique à tout le système scolaire.

The Integration of the New Information and Communication Techologies in the English Schools of Québec - Advisory Board on English Education (1997)
At a time when the reform of education is under way and there is mounting pressure to integrate the new information and communication technologies in schools, the Advisory Board on English Education has tried to identify some of the opportunities for and barriers to an effective implementation of technological developments, in order to allow English schools to take full advantage of the new technologies for the enhancement of learning. To this end we have focused on the four key elements of the educational process most conducive to change: the role of the teacher, student learning, school organization and the need to expand the present technological network throughout the school system.

Cyber Safety : [Do's and Don'ts] - Black Community Resource Centre (BCRC)